Iš lietuvių ir latvių tarmėtyros istorijos: leksikos klausimai Eduardo Volterio programose - Mikulėnienė, Danguolė; Stafecka, Anna (Baltistica, 2011)
FROM THE HISTORY OF LITHUANIAN AND LATVIAN DIALECTOLOGY STUDIES: ISSUES OF LEXIS IN EDUARD VOLTER’S PROGRAMMESGeolinguistic research into the lexis of the Lithuanian and Latvian languages should be linked to the first questionnaires of the latter half of the nineteenth century when a comprehensive gathering of folklore, ethnographical and language facts started in the north-western part of the Russian Empire – the present-day Lithuania and Latvia.The article focuses on the first Lithuanian and Latvian programmes drawn up on the initiative of Eduard Volter – „Программа для указания особенностей говоров Литвы и Жмуди” (Санкт Петербург, 1886) that is considered the first questionnaire of Lithuanian dialectal studies and „Programma tautas gara mantu krājējiem“ (Jelgava, 1892) that dealt with the Latvian cultural heritage (ethnography, ethnology, mythology, etc.). Although the programmes are of a different nature, some of the questions are common for both of them. Three common semantic question groups should be distinguished: 1) the names of the nations under research – the Lithuanian (and Žemaitian) as well as the Latvian – and the neighbouring nations (the Belarusians, Russians, Latvians, Lithuanians, and the Kurshes); 2) the names of living quarters (kaimas, kiemas, ulyčia) and of houses and homesteads; 3) issues connected with mythology.The first Lithuanian and Latvian programmes already revealed common semantic lexical groups. A detailed analysis of these programmes creates conditions for further search for parallels in the studies of Lithuanian and Latvian.
Keywords: lietuvių - latvių; tarmėtyra